Rule-formulation and binding precedent in the madhhab-law tradition : Ibn Qutlubugha's commentary on the compendium of Quduri - Al-Azem, Talal. (Islamicate Intellectual History, 2016)
In Rule-Formulation and Binding Precedent in the Madhhab-Law Tradition , Talal Al-Azem argues for the existence of a madhhab -law tradition' of jurisprudence underpinning the four post-classical Sunni schools of law. This tradition celebrated polyvalence by preserving the multiplicity of conflicting opinions within each school, while simultaneously providing a process of rule formulation ( tarjīḥ ) by which one opinion is chosen as the binding precedent ( taqlīd ). The predominant forum of both activities, he shows, was the legal commentary. Through a careful reading of Ibn Quṭlūbughā's (d. 879/1474) al-Taṣḥīḥ wa-al-tarjīḥ , Al-Azem presents a new periodisation of the Ḥanafī madhhab , analyses the theory of rule formulation, and demonstrates how this madhhab -law tradition facilitated both continuity and legal change while serving as the basis of a pluralistic Mamluk judicial system.